European works councils: a trade union guide to Directive 2009/38/EC - Picard, Séverine (Brussels, 2010)
"This guide has been developed by the ETUC in order to help trade unionists and practitioners in the area of information and consultation around Europe to play an active role in this process and to make the most of the new provisions in the European Works Council Directive as amended by Directive 2009/38/EC. It is an article-by-article legal commentary, written in an accessible style so that it can be used by everybody with interest in European Works Councils and their functioning. Part I contains general remarks on objectives and principles. Parts II, III and IV contain an article by article analysis of the provisions of the Directive and their consequences."